2020
DOI: 10.4236/ojepi.2020.102017
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of COVID-19 in Relation to Public Health Countermeasures in Morocco

Abstract: The new coronavirus, officially responsible for COVID-19, has spread rapidly internationally despite multiple countermeasures to limit its transmission. Morocco recorded his first case of COVID-19 on March 02, 2020. The main data on the pandemic and its evolution come from the Moroccan Ministry of Health. This paper aims to describe the evolution of the pandemic in Morocco and to highlight the different measures taken to stem its progression between March 02 to April 07, 2020. The measures were taken very earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The novel coronavirus responsible for COVID-19 has spread aggressively over the world (Sebbani et al 2020 ). The increasing uncertainty caused by the pandemic has substantially impacted many countries’ cultures and economies (Janadari 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The novel coronavirus responsible for COVID-19 has spread aggressively over the world (Sebbani et al 2020 ). The increasing uncertainty caused by the pandemic has substantially impacted many countries’ cultures and economies (Janadari 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These measures have helped to flatten the curve of contaminated cases relative to neighbouring countries (Sebbani et al, 2020), but the prospects for the spread of the pandemic remain alarming (Layelmam et al, 2020) and the socio-economic impacts have been as significant as those identified internationally (Nicola et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In Morocco, drastic public health countermeasures were implemented starting from March 2020 11 . The public health sector has taken the entire responsibility of fighting the pandemic by restructuring and reorganising its services with the intention of expeditiously diagnosing and treating those affected by the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In Morocco, drastic public health countermeasures were implemented starting from March 2020. 11 The public health sector has taken the entire responsibility of fighting the pandemic by restructuring and reorganising its services with the intention of expeditiously diagnosing and treating those affected by the disease. Meanwhile, as non-COVID-19-related medical need persists, the medical activity continues in both the public and private sector and healthcare workers continue to be at high risk for contracting the virus in the course of their clinical duties towards patients.…”
Section: Introductionmentioning
confidence: 99%